Folic Acid From Supplements or Fortified Foods Consumed During Pregnancy and/or Lactation and Health Outcomes in Mothers and Their Children: A NESR Systematic Review. (7th June 2021) - Nevins, Julie; Spill, Maureen; Donovan, Sharon M; Dewey, Kathryn; Novotny, Rachel; Stang, Jamie; Taveras, Elsie; Kleinman, Ronald; Raghavan, Ramkripa; Scinto-Madonich, Sara; Kim, Julia; Butera, Gisela; et al.
Abstract: Objectives: To inform the Dietary Guidelines for Americans, 2020–2025, USDA and HHS identified the following important public health question for the 2020 Dietary Guidelines Advisory Committee to answer with support from USDA's Nutrition Evidence Systematic Review (NESR) team: What is the relationship between folic acid from supplements and/or fortified foods consumed before and during pregnancy and lactation and health outcomes? Methods: The Committee developed protocols to describe how they would use NESR's systematic review methodology to examine the evidence. NESR conducted a literature search and dual-screened the results using pre-defined inclusion and exclusion criteria for articles published between 1980 and 2019. NESR extracted data and assessed risk of bias of included studies. The Committee synthesized the evidence, developed conclusion statements, and graded the strength of the evidence underlying the conclusion statements. Results: This systematic review included 30 articles, most of which were well-designed RCTs. Observational studies had risk of bias concerns. The study populations did not fully represent the diversity of the U.S. population. Conclusions: Strong evidence indicates that folic acid supplements consumed before and/or during pregnancy are positively associated with folate status. Moderate evidence indicates that folic acid supplements consumed during lactation are positively associated with folate status. Limited evidence suggests that folic acid supplements consumed during early pregnancy may have a beneficial effect on reducing the risk of hypertensive disorders during pregnancy among women at high-risk versus no supplementation. Moderate evidence indicates that higher versus lower levels of folic acid supplements consumed during pregnancy does not affect the risk of hypertensive disorders during pregnancy among women at low-risk. Moderate evidence indicates that folic acid supplements consumed during lactation does not influence folate levels in human milk. Insufficient or no evidence was available to examine folic acid and gestational diabetes or child developmental, or folic acid from fortified foods and any outcome. Funding Sources: USDA, Food and Nutrition Service, Center for Nutrition Policy and Promotion.